RESPONS MORFOLOGI BENIH KARET (Hevea brasiliensis Muell Arg.) TANPA CANGKANG TERHADAP PEMBERIAN PEG 6000 DALAM PENYIMPANAN PADA DUA MASA PENGERINGAN - Gustiansyah Perdhana Putra; Charloq Charloq; Jasmani Ginting (Universitas Sumatera Utara, 2013)
ABSTRACTMorphological response of shelled rubber seed (Hevea brasilliensis Muell Arg.) by givingPolyethylene Glycol (PEG) 6000 in storage at two drying period. Rubber seeds arerecalcitrant seeds that have a high water content so it can not be stored longer because rapiddeteriorated so it needs special handling to increase storability. PEG 6000 is a compound thatcan help maintain seed viability in storage because has the potential osmoticum, which canlimit the imbibition and diffusion processes. Research purposes was to determine theconcentration of PEG and seed drying time appropriate to improve storability the seeds.Research conducted in the Seed Technology Laboratory, Agricultural Faculty, SumateraUtara University in January to March 2012. Nested factorial experiment was arranged in atwo-stage nested design namely time drying as nested factor (drying time at 00:00 am to06:00 am and 6:00 am to 12:00 am) and PEG 6000 (w/v) concentration factor as sub nest(0%, 15%, 30%, 45% ). Parameters namely observed in seed storage fungal andrecapitulation seeds germinated after storage. The results showed that fungal seeds in storageat a concentration of 15% PEG can reduce up to 13,33% with seed germination to 87,13 %and fungal seeds in storage at drying time at 06:00 am to 12:00 am can reduce up to 6.83%with recapitulation seed germination after storage to 93,74%.Key words: rubber seeds, time drying, PEG 6000